Hopper-skeletal and hemispherical crystallization of graphite in iron–carbon–silicon alloys. (30th August 2020) - Stefanescu, D.M.; Alonso, G.; Gonzalez, R.; Suarez, R.
Abstract: The growth of graphite during solidification and solid-state transformation of Fe–C–Si alloys continues to be the subject of extensive research. This is particularly valid for spheroidal graphite, as control of graphite shape is vital to achieving the level of performance required in contemporary applications of these casting alloys. For irons solidifying in the stable system, growth of spheroidal graphite typically starts in the liquid before the eutectic reaction, and then continues through carbon diffusion from the liquid to the austenite through an austenite shell, to finally being completed through growth in solid state because of decreased carbon solubility during cooling or iron carbide decomposition if metastable solidification also occurs. The process may be complicated by partial or even complete metastable solidification. This last scenario is typical for industrial malleable iron. To further understand graphite growth mechanisms, irons of similar composition but with four level of Mg (<0.01–0.047%) were rapidly solidified in copper molds to produce samples with metastable eutectic. The samples were annealed at 950 °C for 4–40 min to promote graphite growth, and then quenched in water. Optical and scanning electron microscopy on polished and deep etched specimens was used to study the growth kinetics of nucleation and growth of graphite. Sequential nucleation of graphite on complex Mg sulfides that have nucleated on Mg oxides was documented. Unique features such as honeycomb structure typical for hopper skeletal-type crystals analogous to ice crystals, and hemispherical growth of graphite aggregates in Fe–C–Si alloys were observed and documented. The experimental findings are additional support of the multi-mechanism theory of graphite growth in iron alloys. Graphical abstract: Image 1